Designing a System Dynamics model to simulate criteria affecting oil and gas development contracts. (September 2022) - Hendalianpour, Ayad; Liu, Peide; Amirghodsi, Sirous; Hamzehlou, Mohammad
Abstract: One of the policies taken by host countries to provide huge funds, and modern technical and managerial knowledge, and convey high risks of the exploitation and development of oil and gas reserves is cooperating with international oil and gas companies through different types of contracts. This study aimed at identifying the impact of all factors affecting oil and gas field development contracts, while considering all aspects in an integrated manner. As, System Dynamics (SD) can simultaneously demonstrate the combined effects of economic, legal, technical, technological, and social sections of a contract on the project objectives, and dynamically reflects the risks of parties in each type of contract over time, SD is used as a contribution in research method to not only examine the current system conditions but also to simulate the future conditions of the system under different scenarios while considering all factors simultaneously. The results revealed that from 5 defined scenarios, While Scenario 1 utilizing a concession agreement is considered as the most inappropriate one for national oil companies, Scenario 5 which utilizes a Service Contract (SC) is the most attractive one for the host countries. The results also show that scenario 3 benefiting from a production sharing contract offers a win-win situation for both parties and it facilitates productivity enhancement strategies for the host country. Highlights: Applying SD to analyze the performance of different types of OAGFDC and partners' risks in different scenarios. All factors affecting the OAGFDC are simultaneously considered to facilitate a precise policy-making procedure. Able to simulate the future conditions of the system in different scenarios over time. Production sharing contracts are tracked as a win-win scenario, both for host and IOCs. While SCs are the most desirable contracts for host countries, concession agreements are the most inappropriate ones.